Strategi Harga Bakso Malang Saat Kenaikan Bahan Baku di Lingkungan Kampus UPB - Nabilah Dwi Ananda; Nisa Azzahra; Pupung Purnamasari (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to explore the pricing strategies adopted by Bakso Malang vendors around the Universitas Pelita Bangsa (UPB) campus in response to rising production costs. The research employs a descriptive qualitative approach with a case study design, utilizing data collection techniques such as semi-structured interviews, non-participant observation, and documentation, with data validation through source triangulation. The findings reveal that the vendors implement three primary strategies: (1) cost-based pricing to ensure production costs are covered, (2) price adjustment through portion or quality reduction (downsizing), and (3) value-based pricing that reflects consumer perception of product worth. These findings offer significant contributions to the literature on micro and small enterprise (MSE) pricing strategies by highlighting the socio-cultural and psychological dimensions often overlooked in quantitative approaches. The practical implications emphasize the need for context-sensitive pricing flexibility and the importance of supportive policies that adapt to market dynamics.